2023
DOI: 10.1002/lpor.202300537
|View full text |Cite
|
Sign up to set email alerts
|

GHz Figure‐9 Er‐Doped Optical Frequency Comb Based on Nested Fiber Ring Resonators

Xinru Cao,
Jiaqi Zhou,
Zhi Cheng
et al.

Abstract: The field of optical‐frequency‐combs (OFCs) has seen significant progress in recent years due to the advance of mode‐locked fiber lasers with low‐noise performance and long‐term reliability. With the emergence of applications, OFCs with repetition rates close to GHz have become highly sought after. However, generating GHz fiber‐based combs with low noise remains a significant challenge. In this study, a GHz figure‐9 Er‐doped OFC based on a nested fiber ring resonator is presented. By matching the free‐spectral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In 2023, Cao et al adopted a metho achieve a repetition rate of GHz in a laser cavity. An optical cavity was nested in an bium-doped fiber laser based on NALM to achieve a repetition rate of 907 MHz, and SNR of fceo was only about 30dB at a RBW of 10 kHz [92], as shown in Figure 5. However, compared with an NPR-based fiber laser [88,89] and a SESAM-based laser [44,90], the repetition rate of the NALM-based laser cavity has difficulty reaching above GHz due to the limitation of the mode-locking principle.…”
Section: Nalm-based Er:fiber Optical Frequency Combmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2023, Cao et al adopted a metho achieve a repetition rate of GHz in a laser cavity. An optical cavity was nested in an bium-doped fiber laser based on NALM to achieve a repetition rate of 907 MHz, and SNR of fceo was only about 30dB at a RBW of 10 kHz [92], as shown in Figure 5. However, compared with an NPR-based fiber laser [88,89] and a SESAM-based laser [44,90], the repetition rate of the NALM-based laser cavity has difficulty reaching above GHz due to the limitation of the mode-locking principle.…”
Section: Nalm-based Er:fiber Optical Frequency Combmentioning
confidence: 99%
“…In 2023, Cao et al adopted a method to achieve a repetition rate of GHz in a laser cavity. An optical cavity was nested in an Erbium-doped fiber laser based on NALM to achieve a repetition rate of 907 MHz, and the SNR of f ceo was only about 30dB at a RBW of 10 kHz [92], as shown in Figure 5.…”
Section: Nalm-based Er:fiber Optical Frequency Combmentioning
confidence: 99%
See 1 more Smart Citation
“…wing to the widespread applications in both scientific research and industries such as frequency combbased spectroscopy, [1][2][3] laser processing, 4,5) and bio-imaging, 6) high repetition rate fiber lasers have been developed intensively and many breakthroughs have been achieved. Techniques such as active mode-locking, 7) passively harmonic mode-locking, 8,9) dissipative four-wave mixing 10) and mode filtering 11) could achieve a very high repetition rate, however, they exhibit a higher instability in terms of output performance compared to fundamentally passive mode-locking. 12) Previous works have shown that ultrahigh repetition rates can be obtained by using short fiber Fabry-Perot resonators.…”
mentioning
confidence: 99%